Criollos contra peninsulares: la bella leyenda - Tomás Pérez Vejo (Les Cahiers ALHIM)
This article analyzes the role that clashes between “Criollos” and “Peninsulares” played in the development of Hispano-American independence wars. After showing that they had a marginal role in these conflicts, it develops the hypothesis that the insistence of different national historiographies in seeing these clashes as the main cause of independence wars is to be explained by their interpretation of these wars as national liberation wars rather than civil wars.